Mechanism of Action of Zhi Gan Cao Decoction for Atrial Fibrillation and Myocardial Fibrosis in a Mouse Model of Atrial Fibrillation: A Network Pharmacology-Based Study. (9th June 2022) - Gao, Lei; Kan, Chenjing; Chen, Xin; Xu, Shengsong; Shi, Kaihu
Abstract : Atrial fibrillation (AF), a commonly seen cardiac disease without optimal curative treatment option, is usually treated by traditional Chinese medicine in China. The Zhi-Gan-Cao decoction (ZGCD) is an alternative medicine for clinical use and has definitive effects. It remains to be defined regarding the specific components and related mechanisms of ZGCD for the treatment of AF. We determined the primary constituents and major targets of the herbs in ZGCD using the TCMSP, HERB, and BATMAN-TCM databases. The UniProt databank database amended and combined the prospective names to supply objective data and records. Every target connected to AF was generated using the GeneCards databank, Drugbank database, TTD, Disgenet database, and OMIM. After identifying possible common targets between ZGCD and AF, the interface network illustration "ZGCD component-AF-target" was created using Cytoscape. We obtained 175 constituents and 839 targets for seven herbal drug categories in the ZGCD and identified 1008 targets of AF. After merging and removing repetitions, 136 collective targets between the ZGCD and AF were removed using the Cytoscape system. These renowned targets were generated from 38 suitable components from among the 157 components. GO enhancement examination and KEGG enrichment analysis by Metascape identified the close connection between the critical target genes and 20 signaling pathways. Then, we injected isoproterenol subcutaneously into the mouse and gave gavage with roasted licorice soup. Two weeks later, mouse were processed and sampled for testing. The results of HE and Masson staining showed that ZGCD effectively alleviated the degree of myocardial fibrosis. As indicated by qRT-PCR and Western blotting, ZGCD significantly reduced COL1A1, COL1A2, COL3A1, and TGF- β 1 in myocardial fibrotic tissue to reduce myocardial fibrosis and treat AF by interfering with the expression of COL1A1, COL1A2, COL3A1, and TGF- β 1 in myocardial tissue. ZGCD may treat AF by lowering the degree of myocardial fibrosis.